Snowmelt contribution to Arctic first-year ice ridge mass balance and rapid consolidation during summer melt - Lange, Benjamin A.; Salganik, Evgenii; Macfarlane, Amy; Schneebeli, Martin; Høyland, Knut Vilhelm; Gardner, Jessie; Müller, Oliver; Divine, Dmitry; Kohlbach, Doreen; Katlein, Christian; Granskog, Mats (Elem Sci Anth, 2023)
An assessment of potential groundwater areas in the Ifni basin, located in the western AntiAtlas range of Morocco, was conducted based on a multicriteria analytical approach that integrated a set of geomorphological and hydroclimatic factors influencing the availability of this resource. This approach involved the use of geographic information systems (GIS) and hierarchical analytical process (AHP) models. Different factors were classified and weighted according to their contribution to and impact on groundwater reserves. Their normalized weights were evaluated using a pairwise comparison matrix. Four classes of potentiality emerged: very high, high, moderate, and low, occupying 15.22%, 20.17%, 30.96%, and 33.65%, respectively, of the basin’s area. A groundwater potential map (GWPA) was validated by comparison with data from 134 existing water points using a receiver operating characteristic (ROC) curve. The AUC was calculated at 80%, indicating the good predictive accuracy of the AHP method. These results will enable water operators to select favorable sites with a high groundwater potential.